Comparative Transcriptomic Analyses Identify Candidate Genes for Convergent Reproductive Shifts in a Bimodal Viviparous Amphibian - Kevin P. Mulder; André Lourenço; Ivan Gomez‐Mestre; Miguel Carneiro; David Buckley; Iñigo Martínez‐Solano; Robert C. Fleischer; Rayna C. Bell; Guillermo Velo‐Antón (Molecular Ecology, 2026)
Shifts in reproductive mode represent key evolutionary innovations that shape species' life histories and evolutionary trajectories. Species showing bimodal reproductive strategies with multiple independent origins offer a rare opportunity to gain insights into the adaptive processes and mechanisms underlying convergent traits. The fire salamander, Salamandra salamandra , is the only amphibian exhibiting intraspecific variation in reproductive mode across multiple independent reproductive shifts, enabling investigation of the transition between larviparity (females give birth to aquatic larvae) and pueriparity (females give birth to fully developed terrestrial juveniles) within a single species and across different timescales. Pueriparity is an adaptive innovation that skips the aquatic larval stage, allowing individuals to exploit habitats with no available water bodies. The fire salamander is larviparous across most of its range, but pueriparity has evolved independently at least three times: once in the early Pleistocene within S. s. bernardezi in the mountains of northern Spain, and more recently on two land‐bridge islands (NW Spain) inhabited by S. s. gallaica . To identify candidate genes associated with these distinct reproductive modes, we compared gene expression profiles of the uterus and oviduct of pregnant females across two independent evolutionary transitions using RNA‐sequencing. We detected shared changes in maternal gene expression among pueriparous S. s. bernardezi and S. s. gallaica relative to their larviparous counterparts, in addition to differences unique to each independent evolutionary transition. Functional enrichment analyses indicated that differentially expressed genes were associated with reproductive timing, angiogenesis, and maternal signalling, consistent with the phenotypic differences observed in the uterine environment and embryonic development between the two reproductive modes. This study represents an important first step towards understanding the genomic basis of the evolution of pueriparity in a remarkable bimodal reproductive system, and provides transcriptomic resources and candidate genes for future research into the genomic architecture underlying this poorly understood adaptive trait.

Molecular characterization of Cdh12-SCON conditional knockout mice reveals unexpected splicing changes - Mayke A. C. ten Hoor; Margot M. Linssen; Conny M. Brouwers; Jill W. C. Claassens; Jaap Mulder; Peter Hohenstein (Transgenic Research, 2026)
Functional validation of candidate genes in congenital anomalies of the kidneys and urinary tract (CAKUT) and other disorders is essential for translating genetic discoveries into clinical applications. Conditional knockout mouse models are indispensable for studying gene function in complex organ systems. The Short Conditional intrON (SCON) system accelerates the generation of such models by inserting the artificial SCON into a coding exon. SCON is designed to be spliced out after transcription, without affecting gene expression. Upon Cre activity, SCON is converted into the ΔSCON allele which cannot be spliced out, introducing premature termination codons (PTCs) to inactivate the gene. Previous validation of the SCON system in mice has focused primarily on phenotypic outcomes. Here, we provide a molecular characterization of the SCON system in Cdh12—a candidate gene implicated in kidney damage in CAKUT. We found that both Cdh12 SCON and Cdh12 ΔSCON alleles caused unintended skipping of the exon downstream of the insertion site, culminating in a frameshift and PTC. Consequently, the Cdh12 SCON allele led to a ~ 25% reduction in mRNA expression, indicating that it was not transcriptionally inert as designed. Despite unintended exon skipping, the Cdh12 ΔSCON allele still effectively suppressed mRNA expression. These findings highlight the importance of transcript-level characterization of engineered alleles prior to functional studies, as artefactual splicing events may occur across multiple gene-targeting strategies, including artificial intron-based conditional alleles as shown here.

Permo-Triassic rift nucleation in East Antarctica revealed by low-temperature thermochronology - Ferdinand Mayer-Ullmann; Stijn Glorie; Martin Hand; Samuel C. Boone; Angus Nixon; Martin Danišík; Jacqueline A. Halpin; Jacob A. Mulder (Earth and Planetary Science Letters, 2026)

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Continental‐Scale Evidence of Farm Management Impacts on Soil Carbon - Julian Helfenstein; Nick van Dijk; Anna Edlinger; Gabriel Y. K. Moinet; Sophie Q. van Rijssel; Alexandre M. J.‐C. Wadoux; Rachel Creamer; Carmen Vazquez; Vera L. Mulder (Global Change Biology, 2026)
There are high expectations that agricultural practices can mitigate climate change and improve soil health by increasing soil organic carbon (SOC) stocks. However, existing large scale SOC monitoring treats agricultural management as a black box, meaning that observed patterns and trends cannot inform on the option space of agricultural practices to improve or deteriorate SOC stocks. Here, we combine for the first time management data from large scale systematic farm surveys ( n = 248,362 farms) and representative soil monitoring data ( n = 8834 locations) to quantify the impact of agricultural practices on three SOC metrics across all pedoclimatic zones of Europe (EU + UK): stocks, stocks relative to pedoclimatic benchmarks, and yearly change in SOC concentration. Our findings show that in arable and tree crops, but not in grasslands, management intensity is a significant contributor to SOC loss, with impact varying by soil and climate region. However, we also observed that several practices (e.g., high share of manure, organic management, and a high proportion of leys in crop rotation) demonstrated potential for increasing SOC stocks. Under a scenario where all agricultural land in Europe would be managed as that of the 10% most optimally managed farms in terms of SOC benefit, SOC stocks would increase by 1.58 Pg C across Europe (95% CI: 1.27–1.89 Pg C). Whereas under a scenario where farms are managed as the 10% least optimally managed farms, SOC would decrease by −0.92 Pg C (−1.15 to −0.68 Pg C). However, it is important to note that these estimates reflect steady‐state SOC stocks only (i.e., they do not represent the transient build‐up or loss over time, or interactions with a changing climate). This paper thus quantifies how agricultural practices influence patterns in SOC stocks at the continental scale, identifying leverage points for site‐specific policies to improve SOC stocks.

“I care but it doesn't keep me up at night”: A qualitative exploration of perceptions of biodiversity-friendly food consumption - Julia Q. Shen; Jonas House; Bob C. Mulder; Sigrid Wertheim-Heck (Appetite, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Whole-genome characterisation of Escherichia coli isolates from older women with urinary tract infection and asymptomatic bacteriuria - Marlies Mulder; Manu P. Bilsen; Martha T. van der Beek; Antoni P. A. Hendrickx; Angela de Haan; Merel M. C. Lambregts; Caroline Schneeberger-van der Linden (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Within patient horizontal gene transfer dynamics of a blaNDM−7 plasmid among four different bacterial species - O. van Katwijk; M. Mulder; L. van Alphen; F. Landman; A. Hendrickx; A. Verkerk; L. Sligman; R. Schnabel; W. van der Zwet; E. Smeets; JAMC. Dirks; C. Jamin (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose We describe the case of a 73-year old male who was found to be a carrier of an bla NDM -producing Citrobacter freundii shortly after admission. During his admission, he developed abdominal abscesses and received multiple courses of piperacillin-tazobactam. In the following months, he was found to carry three other carbapenemase-positive species: Klebsiella oxytoca , Raoultella planticola and Serratia marscescens . Results Two of these strains had clustering carbapenem-sensitive isolates cultured before. The species all carried an bla NDM−7 encoding incX3 plasmid, which demonstrated horizontal gene transfer within this patient. Conclusion This case report underlines the importance of mobile genetic elements in infection control, as they serve as transmission vehicles for antimicrobial resistance beyond the spread of identical bacterial strains.

First insights into soil fauna mapping across Europe using data from multiple data sources for three different taxa - Flore Marchal; Maria Tsiafouli; Alexandre M.J.-C. Wadoux; Maria J.I. Briones; Cristina Fiera; Paul Henning Krogh; Ladislav Miko; Christian Mulder; Maria Papadopoulou; Anton Potapov; David Russell; Lucia Santorufo; et al. (Applied Soil Ecology, 2026)

Corrigendum to “Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets” [Applied Soil Ecology 204 (2024) 105710] - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2026)

P05-01 Chronic dioxin exposure aggravates endothelial damage and left ventricular diastolic dysfunction only in male obese mice - G. Berge; R. Courcoux; M. Quétin; C. Dubois; F. Relaix; P. Mulder; M. Mericskay; M. Gervais (Toxicology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2024)

An innovative model-based protocol for minimisation of greenhouse gas (GHG) emissions in WRRFs - S. Daneshgar; Y. Amerlinck; A. Amaral; C. De Mulder; A. Di Nisio; G. Bellandi; R. Gori; C. Caretti; I. Ducci; U. Rehman; J. Porro; I. Nopens; et al. (Chemical Engineering Journal, 2024)

Interactions Between Heavy Metal Exposure and Blood Biochemistry in an Urban Population of the Black Swan (Cygnus atratus) in Australia - Damien Nzabanita; Raoul A. Mulder; Damian C. Lettoof; Stephen Grist; Jordan O. Hampton; Jasmin Hufschmid; Dayanthi Nugegoda (Archives of Environmental Contamination and Toxicology, 2024)
There is growing recognition of the threat posed to wildlife by pollutants. Waterbirds are robust bioindicators of ecosystem health, and metal toxicity is a threat to these species in waterways worldwide. Urban waterbirds are likely to be at the highest risk of heavy metal exposure, but this issue has not been widely explored in Australia. Our aim was to estimate contemporary heavy metal exposure in a sedentary urban waterbird population: black swans ( Cygnus atratus ) inhabiting an inner-city wetland in one of Australia’s largest cities, Melbourne. To investigate the physiological implications of legacy heavy metal exposure in these birds, we quantified blood biochemistry profiles and examined their relationships with metal concentrations in feathers. We caught 15 swans in 2021 and took feather samples to measure the concentration of eight heavy metals (chromium (Cr), manganese (Mn), iron (Fe), nickel (Ni), copper (Cu), zinc (Zn), lead (Pb), and mercury (Hg)), and blood samples to measure the concentration of 13 plasma analytes. Multivariate regression analysis revealed few associations between heavy metals and biochemistry markers, and no differences between sexes or age classes. This study presents a baseline dataset of these contaminants and blood biochemical profiles of swans at this wetland that can be used for future monitoring and is an important step toward a better understanding of the threat posed by heavy metals to Australian urban waterbirds.

Hand-feel soil texture observations to evaluate the accuracy of digital soil maps for local prediction of soil particle size distribution: A case study in Central France - Anne C. RICHER-de-FORGES; Dominique ARROUAYS; Laura POGGIO; Songchao CHEN; Marine LACOSTE; Budiman MINASNY; Zamir LIBOHOVA; Pierre ROUDIER; Vera L. MULDER; Hervé NÉDÉLEC; Guillaume MARTELET; Blandine LEMERCIER; et al. (Pedosphere, 2023)

Friends near and afar, through thick and thin: Comparing contingency of help between close-distance and long-distance friends in Tanzanian fishing villages - Kristopher M. Smith; Anne C. Pisor; Bertha Aron; Kasambo Bernard; Paschal Fimbo; Rose Kimesera; Monique Borgerhoff Mulder (Evolution and Human Behavior, 2023)

Occurrence and associated health risks of pyrrolizidine alkaloids in supplements marketed in Ghana for improved sexual performance - Felicia Akuamoa; Patrick P. J. Mulder; Toine F. H. Bovee; Ivonne M. C. M. Rietjens; Ron L. A. P. Hoogenboom (Food Additives & Contaminants Part B-Surveillance, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

A molten salt test loop for component and instrumentation testing - T.L. Head; Allison M. Berry; Keaton J. Brewster; Robert L. Brown; Hailey N. Burden; Reuben Byrd; Timothy Doty; Jess Dowdy; Kameron A. Hill; R.A. Jinkerson; Timothy J. Kennedy; Ronald C. Laehn; et al. (Annals of Nuclear Energy, 2023)

Quaternary sedimentary processes on the Bahamas: From platform to abyss - K. Fauquembergue; E. Ducassou; T. Mulder; J.J.G. Reijmer; J. Borgomano; A. Recouvreur; V. Hanquiez; C. Betzler; M. Principaud; L. Chabaud; N. Fabregas; J. Giraudeau; et al. (Marine Geology, 2023)

Consent Codes: Maintaining Consent in an Ever-expanding Open Science Ecosystem - Stephanie O. M. Dyke; Kathleen Connor; Victoria Nembaware; Nchangwi S. Munung; Kathy Reinold; Giselle Kerry; Mamana Mbiyavanga; Lyndon Zass; Mauricio Moldes; Samir Das; John M. Davis; Jordi Rambla De Argila; et al. (Neuroinformatics, 2023)
We previously proposed a structure for recording consent-based data use ‘categories’ and ‘requirements’ – Consent Codes – with a view to supporting maximum use and integration of genomic research datasets, and reducing uncertainty about permissible re-use of shared data. Here we discuss clarifications and subsequent updates to the Consent Codes (v4) based on new areas of application (e.g., the neurosciences, biobanking, H3Africa), policy developments (e.g., return of research results), and further practical considerations, including developments in automated approaches to consent management.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Speciation with gene flow in a narrow endemic West Virginia cave salamander (Gyrinophilus subterraneus) - Evan H. Campbell Grant; Kevin P. Mulder; Adrianne B. Brand; Douglas B. Chambers; Addison H. Wynn; Grace Capshaw; Matthew L. Niemiller; John G. Phillips; Jeremy F. Jacobs; Shawn R. Kuchta; Rayna C. Bell (Conservation Genetics, 2022)

Bioassay-directed analysis-based identification of relevant pyrrolizidine alkaloids - Jochem Louisse; Patrick P. J. Mulder; Arjen Gerssen; Geert Stoopen; Deborah Rijkers; Milou G. M. van de Schans; Ad A. C. M. Peijnenburg (Archives of Toxicology, 2022)
Pyrrolizidine alkaloids (PAs) are produced by various plant species and have been detected as contaminants in food and feed. Monitoring programmes should include PAs that are present in relevant matrices and that exhibit a high toxic potential. The aim of the present study was to use a bioassay-directed analysis approach to identify relevant PAs not yet included in monitoring programmes. To that end, extracts of Heliotropium europaeum and H. popovii were prepared and analysed with LC–MS/MS for the presence of 35 PAs included in monitoring programmes, as well as for genotoxic activity in the HepaRG/γH2AX assay. Europine, heliotrine and lasiocarpine were found to be the most abundant PAs. The extracts showed a higher γH2AX activity than related artificial mixtures of quantified known PAs, which might point to the presence of unknown toxic PAs. The H. europaeum extract was fractionated and γH2AX activities of individual fractions were determined. Fractions were further analysed applying LC–Orbitrap-MS analysis and Compound Discoverer software, identifying various candidate PAs responsible for the non-explained genotoxic activity. Altogether, the results obtained show that bioassay-directed analysis allows identification of candidate PAs that can be included in monitoring programmes.

Manual delineation approaches for direct imaging of the subcortex - Anneke Alkemade; Martijn J. Mulder; Anne C. Trutti; Birte U. Forstmann (Brain Structure and Function, 2022)
The growing interest in the human subcortex is accompanied by an increasing number of parcellation procedures to identify deep brain structures in magnetic resonance imaging (MRI) contrasts. Manual procedures continue to form the gold standard for parcellating brain structures and is used for the validation of automated approaches. Performing manual parcellations is a tedious process which requires a systematic and reproducible approach. For this purpose, we created a series of protocols for the anatomical delineation of 21 individual subcortical structures. The intelligibility of the protocols was assessed by calculating Dice similarity coefficients for ten healthy volunteers. In addition, dilated Dice coefficients showed that manual parcellations created using these protocols can provide high-quality training data for automated algorithms. Here, we share the protocols, together with three example MRI datasets and the created manual delineations. The protocols can be applied to create high-quality training data for automated parcellation procedures, as well as for further validation of existing procedures and are shared without restrictions with the research community.

Speciation and secondary contact in a fossorial island endemic, the São Tomé caecilian - Kyle A. O’Connell; Ivan Prates; Lauren A. Scheinberg; Kevin P. Mulder; Rayna C. Bell (Molecular Ecology, 2021)
A period of isolation in allopatry typically precedes local adaptation and subsequent divergence among lineages. Alternatively, locally adapted phenotypes may arise and persist in the face of gene flow, resulting in strong correlations between ecologically‐relevant phenotypic variation and corresponding environmental gradients. Quantifying genetic, ecological, and phenotypic divergence in such lineages can provide insights into the abiotic and biotic mechanisms that structure populations and drive the accumulation of phenotypic and taxonomic diversity. Low‐vagility organisms whose distributions span ephemeral geographic barriers present the ideal evolutionary context within which to address these questions. Here, we combine genetic (mtDNA and genome‐wide SNPs) and phenotypic data to investigate the divergence history of caecilians (Amphibia: Gymnophiona) endemic to the oceanic island of São Tomé in the Gulf of Guinea archipelago. Consistent with a previous mtDNA study, we find two phenotypically and genetically distinct lineages that occur along a north‐to‐south axis with extensive admixture in the centre of the island. Demographic modelling supports divergence in allopatry (~300 kya) followed by secondary contact (~95 kya). Consequently, in contrast to a morphological study that interpreted latitudinal phenotypic variation in these caecilians as a cline within a single widespread species, our analyses suggest a history of allopatric lineage divergence and subsequent hybridization that may have blurred species boundaries. We propose that late Pleistocene volcanic activity favoured allopatric divergence between these lineages with local adaptation to climate maintaining a stable hybrid zone in the centre of São Tomé Island. Our study joins a growing number of systems demonstrating lineage divergence on volcanic islands with stark environmental transitions across small geographic distances.

Effects of tetracycline on entomopathogenic nematodes and their bacterial symbionts - M. Clausi; D. Leone; A. Strano; A. Lizio; G. Rappazzo; C. Mulder; E. Conti (Ecotoxicology, 2021)

A probabilistic atlas of the human ventral tegmental area (VTA) based on 7 Tesla MRI data - Anne C. Trutti; Laura Fontanesi; Martijn J. Mulder; Pierre-Louis Bazin; Bernhard Hommel; Birte U. Forstmann (Brain Structure and Function, 2021)
Functional magnetic resonance imaging (fMRI) BOLD signal is commonly localized by using neuroanatomical atlases, which can also serve for region of interest analyses. Yet, the available MRI atlases have serious limitations when it comes to imaging subcortical structures: only 7% of the 455 subcortical nuclei are captured by current atlases. This highlights the general difficulty in mapping smaller nuclei deep in the brain, which can be addressed using ultra-high field 7 Tesla (T) MRI. The ventral tegmental area (VTA) is a subcortical structure that plays a pivotal role in reward processing, learning and memory. Despite the significant interest in this nucleus in cognitive neuroscience, there are currently no available, anatomically precise VTA atlases derived from 7 T MRI data that cover the full region of the VTA. Here, we first provide a protocol for multimodal VTA imaging and delineation. We then provide a data description of a probabilistic VTA atlas based on in vivo 7 T MRI data.

Progression and Classification of Granular Osmiophilic Material (GOM) Deposits in Functionally Characterized Human NOTCH3 Transgenic Mice - Gido Gravesteijn; Leon P. Munting; Maurice Overzier; Aat A. Mulder; Ingrid Hegeman; Marc Derieppe; Abraham J. Koster; Sjoerd G. van Duinen; Onno C. Meijer; Annemieke Aartsma-Rus; Louise van der Weerd; Carolina R. Jost; et al. (Translational Stroke Research, 2020)
CADASIL is a NOTCH3 -associated cerebral small vessel disease. A pathological ultrastructural disease hallmark is the presence of NOTCH3-protein containing deposits called granular osmiophilic material (GOM), in small arteries. How these GOM deposits develop over time and what their role is in disease progression is largely unknown. Here, we studied the progression of GOM deposits in humanized transgenic NOTCH3 Arg182Cys mice, compared them to GOM deposits in patient material, and determined whether GOM deposits in mice are associated with a functional CADASIL phenotype. We found that GOM deposits are not static, but rather progress in ageing mice, both in terms of size and aspect. We devised a GOM classification system, reflecting size, morphology and electron density. Six-month-old mice showed mostly early stage GOM, whereas older mice and patient vessels showed predominantly advanced stage GOM, but also early stage GOM. Mutant mice did not develop the most severe GOM stage seen in patient material. This absence of end-stage GOM in mice was associated with an overall lack of histological vascular pathology, which may explain why the mice did not reveal functional deficits in cerebral blood flow, cognition and motor function. Taken together, our data indicate that GOM progress over time, and that new GOM deposits are continuously being formed. The GOM staging system we introduce here allows for uniform GOM deposit classification in future mouse and human studies, which may lead to more insight into a potential association between GOM stage and CADASIL disease severity, and the role of GOM in disease progression.

Delineation of phenotypes and genotypes related to cohesin structural protein RAD21 - Lianne C. Krab; Iñigo Marcos-Alcalde; Melissa Assaf; Meena Balasubramanian; Janne Bayer Andersen; Anne-Marie Bisgaard; David R. Fitzpatrick; Sanna Gudmundsson; Sylvia A. Huisman; Tugba Kalayci; Saskia M. Maas; Francisco Martinez; et al. (Human Genetics, 2020)
RAD21 encodes a key component of the cohesin complex, and variants in RAD21 have been associated with Cornelia de Lange Syndrome (CdLS). Limited information on phenotypes attributable to RAD21 variants and genotype–phenotype relationships is currently published. We gathered a series of 49 individuals from 33 families with RAD21 alterations [24 different intragenic sequence variants (2 recurrent), 7 unique microdeletions], including 24 hitherto unpublished cases. We evaluated consequences of 12 intragenic variants by protein modelling and molecular dynamic studies. Full clinical information was available for 29 individuals. Their phenotype is an attenuated CdLS phenotype compared to that caused by variants in NIPBL or SMC1A for facial morphology, limb anomalies, and especially for cognition and behavior. In the 20 individuals with limited clinical information, additional phenotypes include Mungan syndrome (in patients with biallelic variants) and holoprosencephaly, with or without CdLS characteristics. We describe several additional cases with phenotypes including sclerocornea, in which involvement of the RAD21 variant is uncertain. Variants were frequently familial, and genotype–phenotype analyses demonstrated striking interfamilial and intrafamilial variability. Careful phenotyping is essential in interpreting consequences of RAD21 variants, and protein modeling and dynamics can be helpful in determining pathogenicity. The current study should be helpful when counseling families with a RAD21 variation.

Range-wide patterns of human-mediated hybridisation in European wildcats - Annika Tiesmeyer; Luana Ramos; José Manuel Lucas; Katharina Steyer; Paulo C. Alves; Christos Astaras; Mareike Brix; Margherita Cragnolini; Csaba Domokos; Zsolt Hegyeli; René Janssen; Andrew C. Kitchener; et al. (Conservation Genetics, 2020)
Hybridisation between wild taxa and their domestic congeners is a significant conservation issue. Domestic species frequently outnumber their wild relatives in population size and distribution and may therefore genetically swamp the native species. The European wildcat ( Felis silvestris ) has been shown to hybridise with domestic cats ( Felis catus ). Previously suggested spatially divergent introgression levels have not been confirmed on a European scale due to significant differences in the applied methods to assess hybridisation of the European wildcat. We analysed 926 Felis spp. samples from 13 European countries, using a set of 86 selected ancestry-informative SNPs, 14 microsatellites, and ten mitochondrial and Y-chromosome markers to study regional hybridisation and introgression patterns and population differentiation. We detected 51 hybrids (four F1 and 47 F2 or backcrosses) and 521 pure wildcats throughout Europe. The abundance of hybrids varied considerably among studied populations. All samples from Scotland were identified as F2 hybrids or backcrosses, supporting previous findings that the genetic integrity of that wildcat population has been seriously compromised. In other European populations, low to moderate levels of hybridisation were found, with the lowest levels being in Central and Southeast Europe. The occurrence of distinct maternal and paternal markers between wildcat and domestic cat suggests that there were no severe hybridisation episodes in the past. The overall low (< 1%) prevalence of F1 hybrids suggests a low risk of hybridisation for the long-term genetic integrity of the wildcat in most of Europe. However, regionally elevated introgression rates confirm that hybridisation poses a potential threat. We propose regional in-depth monitoring of hybridisation rates to identify factors driving hybridisation so as to develop effective strategies for conservation.

Functional variation at an expressed MHC class IIβ locus associates with Ranavirus infection intensity in larval anuran populations - Anna E. Savage; Carly R. Muletz-Wolz; Evan H. Campbell Grant; Robert C. Fleischer; Kevin P. Mulder (Immunogenetics, 2019)

The use of an electronic clinical rule to discontinue chronically used benzodiazepines and related Z drugs - C. Mestres Gonzalvo; V. Milosevic; B. P. C. van Oijen; H. A. J. M. de Wit; K. P. G. M. Hurkens; W. J. Mulder; R. Janknegt; J. M. G. A. Schols; F. R. Verhey; B. Winkens; P. H. M. van der Kuy (European Journal of Clinical Pharmacology, 2018)

Multiple hypotheses explain variation in extra‐pair paternity at different levels in a single bird family - Lyanne Brouwer; Martijn van de Pol; Nataly Hidalgo Aranzamendi; Glen Bain; Daniel T. Baldassarre; Lesley C. Brooker; Michael G. Brooker; Diane Colombelli‐Négrel; Erik Enbody; Kurt Gielow; Michelle L. Hall; Allison E. Johnson; et al. (Molecular Ecology, 2017)
Extra‐pair paternity ( EPP ), where offspring are sired by a male other than the social male, varies enormously both within and among species. Trying to explain this variation has proved difficult because the majority of the interspecific variation is phylogenetically based. Ideally, variation in EPP should be investigated in closely related species, but clades with sufficient variation are rare. We present a comprehensive multifactorial test to explain variation in EPP among individuals in 20 populations of nine species over 89 years from a single bird family (Maluridae). Females had higher EPP in the presence of more helpers, more neighbours or if paired incestuously. Furthermore, higher EPP occurred in years with many incestuous pairs, populations with many helpers and species with high male density or in which males provide less care. Altogether, these variables accounted for 48% of the total and 89% of the interspecific and interpopulation variation in EPP . These findings indicate why consistent patterns in EPP have been so challenging to detect and suggest that a single predictor is unlikely to account for the enormous variation in EPP across levels of analysis. Nevertheless, it also shows that existing hypotheses can explain the variation in EPP well and that the density of males in particular is a good predictor to explain variation in EPP among species when a large part of the confounding effect of phylogeny is excluded.

Adaptive and neutral genetic differentiation among Scottish and endangered Irish red grouse (Lagopus lagopus scotica) - Yvonne Meyer-Lucht; Kevin P. Mulder; Marianne C. James; Barry J. McMahon; Kieran Buckley; Stuart B. Piertney; Jacob Höglund (Conservation Genetics, 2016)

Effects of non-native Melilotus albus on pollination and reproduction in two boreal shrubs - Katie V. Spellman; Laura C. Schneller; Christa P. H. Mulder; Matthew L. Carlson (Oecologia, 2015)

Air and seawater pollution and air–sea gas exchange of persistent toxic substances in the Aegean Sea: spatial trends of PAHs, PCBs, OCPs and PBDEs - Gerhard Lammel; Ondřej Audy; Athanasios Besis; Christos Efstathiou; Kostas Eleftheriadis; Jiři Kohoutek; Petr Kukučka; Marie D. Mulder; Petra Přibylová; Roman Prokeš; Tatsiana P. Rusina; Constantini Samara; et al. (Environmental Science and Pollution Research, 2015)

Hyper-IgD syndrome/mevalonate kinase deficiency: what is new? - C. M. Mulders-Manders; A. Simon (Seminars in Immunopathology, 2015)

Long-term transmission of measles virus in Central and continental Western Europe - S. Santibanez; J. M. Hübschen; C. P. Muller; F. Freymuth; M. M. Mosquera; M. Ben Mamou; M. N. Mulders; K. E. Brown; R. Myers; A. Mankertz (Virus Genes, 2015)

Territory configuration moderates the frequency of extra‐group mating in superb fairy‐wrens - Glen C. Bain; Michelle L. Hall; Raoul A. Mulder (Molecular Ecology, 2014)
The frequency of extra‐pair paternity ( EPP ) in socially monogamous birds varies substantially between and within species, but ecological drivers of this variation remain poorly understood. Habitat configuration could influence EPP by moderating access to extra‐pair mates, because species occupying territories in a clustered ‘honeycomb’ configuration have a larger pool of potential extra‐group mates in their immediate neighbourhood than those living in linearly arranged territories (e.g. along narrow strips of riparian or fragmented habitat). We exploited variation in the spatial arrangement of territories due to anthropogenic modification of habitat of the cooperatively breeding superb fairy‐wren Malurus cyaneus to test whether habitat configuration influenced the frequency of EPP . In this species, most paternity is obtained by males outside the social group [extra‐group paternity ( EGP )]. We found that the frequency of EGP among groups living in linear strips of roadside vegetation (41% of 44 offspring) was lower than it was for groups living in clustered territories within continuous habitat (59% of 70 offspring). Differences in group size and pair relatedness did not explain differences in EGP associated with territory configuration, although the frequency of EGP was negatively correlated with pair relatedness. Our finding suggests that territory configuration can influence rates of EGP and that anthropogenic habitat fragmentation has the potential to limit access to extra‐pair mates, affecting mating systems and ultimately fitness.

Human Migration, Protected Areas, and Conservation Outreach in Tanzania - JONATHAN D. SALERNO; MONIQUE BORGERHOFF MULDER; SHAWN C. KEFAUVER (Conservation Biology, 2014)
A recent discussion debates the extent of human in‐migration around protected areas (PAs) in the tropics. One proposed argument is that rural migrants move to bordering areas to access conservation outreach benefits. A counter proposal maintains that PAs have largely negative effects on local populations and that outreach initiatives even if successful present insufficient benefits to drive in‐migration. Using data from Tanzania, we examined merits of statistical tests and spatial methods used previously to evaluate migration near PAs and applied hierarchical modeling with appropriate controls for demographic and geographic factors to advance the debate. Areas bordering national parks in Tanzania did not have elevated rates of in‐migration. Low baseline population density and high vegetation productivity with low interannual variation rather than conservation outreach explained observed migration patterns. More generally we argue that to produce results of conservation policy significance, analyses must be conducted at appropriate scales, and we caution against use of demographic data without appropriate controls when drawing conclusions about migration dynamics. La Migración Humana, Áreas Protegidas y el Alcance de la Conservación en Tanzania

Low attack rate of novel influenza A (H1N1) virus infection among healthcare workers: a prospective study in a setting with an elaborated containment plan - Patrick M. Smit; Jan W. Mulder; Mohamed Ahdi; Ron Gerritsen; Stanley Darma; Paul H. M. Smits; Chris Roggeveen; Eric C. M. van Gorp; Guus F. Rimmelzwaan; Dees P. M. Brandjes (International Archives of Occupational and Environmental Health, 2012)

Putative role of the adenosine A3 receptor in the antiproliferative action of N 6-(2-isopentenyl)adenosine - Clara C. Blad; Jacobien K. von Frijtag Drabbe Künzel; Henk de Vries; Thea Mulder-Krieger; Sara Bar-Yehuda; Pnina Fishman; Adriaan P. IJzerman (Purinergic Signalling, 2011)

Patient-Specific Modeling of Cerebral Blood Flow: Geometrical Variations in a 1D Model - G. Mulder; A. Marzo; A. C. B. Bogaerds; S. C. Coley; P. Rongen; D. R. Hose; F. N. van de Vosse (Cardiovascular Engineering and Technology, 2011)

East–west genetic differentiation in Musk Ducks (Biziura lobata) of Australia suggests late Pleistocene divergence at the Nullarbor Plain - P.-J. Guay; R. T. Chesser; R. A. Mulder; A. D. Afton; D. C. Paton; K. G. McCracken (Conservation Genetics, 2010)

General stabilizing effects of plant diversity on grassland productivity through population asynchrony and overyielding - A. Hector; Y. Hautier; P. Saner; L. Wacker; R. Bagchi; J. Joshi; M. Scherer-Lorenzen; E. M. Spehn; E. Bazeley-White; M. Weilenmann; M. C. Caldeira; P. G. Dimitrakopoulos; et al. (Ecology, 2010)
Insurance effects of biodiversity can stabilize the functioning of multispecies ecosystems against environmental variability when differential species' responses lead to asynchronous population dynamics. When responses are not perfectly positively correlated, declines in some populations are compensated by increases in others, smoothing variability in ecosystem productivity. This variance reduction effect of biodiversity is analogous to the risk‐spreading benefits of diverse investment portfolios in financial markets. We use data from the BIODEPTH network of grassland biodiversity experiments to perform a general test for stabilizing effects of plant diversity on the temporal variability of individual species, functional groups, and aggregate communities. We tested three potential mechanisms: reduction of temporal variability through population asynchrony; enhancement of long‐term average performance through positive selection effects; and increases in the temporal mean due to overyielding. Our results support a stabilizing effect of diversity on the temporal variability of grassland aboveground annual net primary production through two mechanisms. Two‐species communities with greater population asynchrony were more stable in their average production over time due to compensatory fluctuations. Overyielding also stabilized productivity by increasing levels of average biomass production relative to temporal variability. However, there was no evidence for a performance‐enhancing effect on the temporal mean through positive selection effects. In combination with previous work, our results suggest that stabilizing effects of diversity on community productivity through population asynchrony and overyielding appear to be general in grassland ecosystems.

Dissimilar response of plant and soil biota communities to long-term nutrient addition in grasslands - A. van der Wal; R. H. E. M. Geerts; H. Korevaar; A. J. Schouten; G. A. J. M. Jagers op Akkerhuis; M. Rutgers; C. Mulder (Biology and Fertility of Soils, 2009)

Three allometric relations of population density to body mass: theoretical integration and empirical tests in 149 food webs - Daniel C. Reuman; Christian Mulder; Dave Raffaelli; Joel E. Cohen (Ecology Letters, 2008)
Predicting species population density–body mass scaling in community food webs (henceforth webs ) is important for conservation and to understand community structure. Very different types of scaling have been studied, based on either individuals or species. The individual size distribution (ISD) describes the distribution of individual‐organism body masses regardless of taxonomy, and contains the same information as the abundance spectrum. Focusing instead on species, the local size–density relationship (LSDR) plots population densities vs. mean body masses of species. The distribution of species mean body masses (the species‐mean‐size distribution , SMSD) is also important but previously little studied in webs. We here combine and formalize theory of several authors to predict: how these three descriptions are related; the forms of the LSDR and ISD; and variation in scaling among webs. We describe empirically the SMSDs of two pelagic, one estuarine, and 146 soil webs by power laws and generalizations. We test theory and find it broadly validated.

Should medical students learn to develop a personal formulary? - T. P. G. M. De Vries; J. M. A. Daniels; C. W. Mulder; O. A. Groot; L. Wewerinke; K. I. Barnes; H. A. Bakathir; N. A. G. M. Hassan; L. Van Bortel; M. Kriska; B. Santoso; E. J. Sanz; et al. (European Journal of Clinical Pharmacology, 2008)

Islet β-cell area and hormone expression are unaltered in Huntington’s disease - Karl Bacos; Maria Björkqvist; Åsa Petersén; Lena Luts; Marion L. C. Maat-Schieman; Raymund A. C. Roos; Frank Sundler; Patrik Brundin; Hindrik Mulder; Nils Wierup (Histochemistry and Cell Biology, 2008)

The SPINK gene family and celiac disease susceptibility - Martin C. Wapenaar; Alienke J. Monsuur; Jos Poell; Ruben van ‘t Slot; Jos W. R. Meijer; Gerrit A. Meijer; Chris J. Mulder; Maria Luisa Mearin; Cisca Wijmenga (Immunogenetics, 2007)

The western part of the Gulf of Cadiz: contour currents and turbidity currents interactions - T. Mulder; P. Lecroart; V. Hanquiez; E. Marches; E. Gonthier; J.-C. Guedes; E. Thiébot; B. Jaaidi; N. Kenyon; M. Voisset; C. Perez; M. Sayago; et al. (Geo-Marine Letters, 2006)

Step characteristics during obstacle avoidance in hemiplegic stroke - A. R. Den Otter; A. C. H. Geurts; M. de Haart; T. Mulder; J. Duysens (Experimental Brain Research, 2005)

Application, eco-physiology and biodiversity of anaerobic ammonium-oxidizing bacteria - Boran Kartal; Laura van Niftrik; Olav Sliekers; Markus C. Schmid; Ingo Schmidt; Katinka van de Pas-Schoonen; Irina Cirpus; Wouter van der Star; Mark van Loosdrecht; Wiebe Abma; J. Gijs Kuenen; Jan-Willem Mulder; et al. (Reviews in Environmental Science and Bio/Technology, 2004)

High sequence diversity in infectious bursal disease virus serotype 1 in poultry and turkey suggests West-African origin of very virulent strains - A. A. Owoade; M. N. Mulders; J. Kohnen; W. Ammerlaan; C. P. Muller (Archives of Virology, 2004)

Incidence and risk factors for nevirapine-associated rash - Monique M. R. de Maat; Rob ter Heine; Jan W. Mulder; Pieter L. Meenhorst; Albert T. A. Mairuhu; Eric C. M. van Gorp; Alwin D. R. Huitema; Jos H. Beijnen (European Journal of Clinical Pharmacology, 2003)

Combination of Vascular Endothelial Growth Factor (VEGF) and Thymidine Phosphorylase (TP) to Improve Angiogenic Gene Therapy - Diane Bouïs; Mirjam C. Boelens; Erna Peters; Pieter Koolwijk; Gerrie Stob; Ido P. Kema; Marco Klinkenberg; Nanno H. Mulder; Geke A.P. Hospers (Angiogenesis, 2003)

The Gulf of Cadiz: an unstable giant contouritic levee - T. Mulder; M. Voisset; P. Lecroart; E. Le Drezen; E. Gonthier; V. Hanquiez; J.-C. Faugres; E. Habgood; F. J. Hernandez-Molina; F. Estrada; E. Llave-Barranco; D. Poirier; et al. (Geo-Marine Letters, 2003)

Optimal Schemes to Detect the Presence of Insect Species - C. Zonneveld; T. Longcore; C. Mulder (Conservation Biology, 2003)
Survey protocols to detect the presence of particular species should be organized to make optimal use of available resources. Current protocols mostly deal with this problem intuitively, but the problem can also be addressed with mathematical modeling. To this aim, we used a model that describes the abundance of a single, discrete generation of adult insects. Furthermore, we assumed that year‐to‐year variation in timing of the flight period was attributable to variation in peak emergence only. We determined the spacing of a given number of survey days on a transect that minimized the chance of missing a species when it was actually present. This spacing was fixed to a Julian date and applied to all years. We also calculated the probability of detecting the species, which depends on the number of survey days. For most parameter values, 5 survey days sufficed to detect with high probability ( ≥0.95 ) populations with an observable population size ( total number of insects that can be observed in the transect over the entire flight period ) exceeding 10. For observable population sizes under 10, achieving a detection probability of 0.95 may require many more than 5 survey days. As an example of the method, we constructed a survey‐detection scheme for the Quino checkerspot butterfly ( Euphydryas editha quino ), based on the limited information available about its flight period. For an observable population size over 11, this scheme had a detection probability openface>0.95. We also provide detection schemes for species whose death rate and variation in emergence time within and between years can at present be characterized only as small, moderate, or large. These survey schemes should maximize species detection and reduce uncertainty about absence.

How plant diversity and legumes affect nitrogen dynamics in experimental grassland communities - C. Mulder; A. Jumpponen; P. Högberg; K. Huss-Danell (Oecologia, 2002)

Reply to discussion by Shanmugam on Mulder et al. (2001, Geo-Marine Letters 21: 86-93) Inversely graded turbidite sequences in the deep Mediterranean. A record of deposits from flood-generated turbidity currents? - Mulder T.; Migeon S.; Savoye B.; Faugères J.-C. (Geo-Marine Letters, 2002)

Local adaptation enhances performance of common plant species - J. Joshi; B. Schmid; M. C. Caldeira; P. G. Dimitrakopoulos; J. Good; R. Harris; A. Hector; K. Huss‐Danell; A. Jumpponen; A. Minns; C. P. H. Mulder; J. S. Pereira; et al. (Ecology Letters, 2001)
Geographic variation can lead to the evolution of different local varieties, even in widespread forage plants. We investigated the performance of common forage plants in relation to their genetic diversity and local adaptation at a continental scale using reciprocal transplants at eight field sites across Europe over a 2‐year period. The overall performance of the three test species, Trifolium pratense , Dactylis glomerata , Plantago lanceolata , was generally highest for plants replanted at their home site and declined with increasing transplanting distance. The three species differed in the fitness components responsible for the increased overall performance and selection advantage at home sites. In addition to the effects of local adaptation, the majority of measured traits in all three species also showed ecotypic variation. However, no single ecotype of any species was able to outperform the locally adapted strains and do best at all sites, highlighting the importance of maintaining these plant genetic resources.

Inversely graded turbidite sequences in the deep Mediterranean: a record of deposits from flood-generated turbidity currents? - Mulder T.; Migeon S.; Savoye B.; Faugres J.-C. (Geo-Marine Letters, 2001)

Molecular epidemiology of echovirus 30 in Europe: succession of dominant sublineages within a single major genotype - C. Savolainen; T. Hovi; M. N. Mulders (Archives of Virology, 2001)

Abstracts of Papers presented at a Workshop on Ecology of Botrytis and Sclerotinia and their Interaction With Other Microorganisms Abstracts of Papers Presented at a Workshop on Genetic Aspects ofFusarium oxysporum and Related Species Abstracts of Papers and Discussion Contributions Presented at the Dutch-Israeli (Diarp) Workshop on Environment-Friendly Crop Protection of the Flower Industry to Suit Future Market Trends - A. Ten Have; W. Oude Breuil; J. Wubben; W. Mulder; J. Visser; J. van Kan; T. Quidde; P. Tudzynski; T. M. O’Neill; G. De Meyer; K. Audenaert; J. Bigirimana; et al. (Phytoparasitica, 1999)

Gene therapy for glioblestome multiforme: in vivo tumor transduction with the herpes simplex thymidine kinase gene followed by ganciclovir - G. Stockhammer; J. Brotchi; R. Leblanc; M. Bernstein; G. Schackert; F. Weber; C. Ostertag; N. H. Mulder; H. Mellstedt; R. Seiler; Y. Yonekawa; K. Twerdy; et al. (Journal of Molecular Medicine, 1997)

Magnesium pyridoxal-5′-phosphate glutamate, "A vitamin B 6 derivative", does not affect lipoprotein levels in patients with familial hypercholesterolaemia - H. C. Knipscheer; I. Kindt; A. van den Ende; M. T. Nurmohamed; H. Smalbraak; W. J. Mulder; J. J. P. Kastelein (European Journal of Clinical Pharmacology, 1997)

Polychlorinated biphenyls, dibenzo-p-dioxins, and dibenzofurans in harbor porpoises (Phocoena phocoena) stranded on the Dutch coast between 1990 and 1993 - W. B. van Scheppingen; A. J. I. M. Verhoeven; P. Mulder; M. J. Addink; C. Smeenk (Archives of Environmental Contamination and Toxicology, 1996)

Comparison of the polymerase region of small round structured virus strains previously classified in three antigenic types by solid-phase immune electron microscopy - T. Ando; M. N. Mulders; D. C. Lewis; M. K. Estes; S. S. Monroe; R. I. Glass (Archives of Virology, 1994)

A cohesive sediment balance for the Scheldt estuary - D. C. Maldegem; H. P. J. Mulder; A. Langerak (Aquatic Ecology, 1993)

Counterimmunoelectrophoresis compared with complement fixation and passive haemagglutination tests in the evaluation of the immune response in Campylobacter infections - J. R. J. Bnffer; J. C. C. Duifhuis; P. G. H. Mulder (Antonie van Leeuwenhoek, 1987)